Relationship between Social Media Addiction and Anxiety among Junior High School Students - Ghozali, Ghozali; Fatma, Fatma; Oktaviani, Lisa Wahidatul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Mental health has many components that can be influenced by various factors. One such factor that can disrupt mental health is anxiety. It is estimated that 4% of the world's population currently suffers from anxiety disorders.Therefore, this study is important to pay attention to the use of social media among students, as it may lead to anxiety and affect the learning process. This study aims to investigate the relationship between social media addiction and anxiety among junior high school students in selected sub-urban area of Samarinda, Indonesia. Method: This study employs a quantitative approach specifically a cross-sectional study. The sample for this study consists of 685 junior high school students. The sampling technique used was cluster random sampling. Data collection was conducted using the BSMAS and DASS-42 questionnaires. The validity of questionnaires using item-total correlation ranged between 0.44 to 0.83 for the BSMAS questionnaire and 0.532 to 0.86 for the DASS-42 questionnaire. Meanwhile, the reliability value with Cronbach's Alpha for each questionnaire was 0.823 for the BSMAS questionnaire and 0.804 for the DASS-42 questionnaire. Based on the Spearman Rank statistical test results, there was a significant relationship between social media addiction and anxiety among junior high school students with a p-value of 0.001 (< 0.05). The correlation coefficient was 0.499, indicating a positive relationship with moderate strength. Schools need to conduct specific educational programs using interesting media to raise awareness about the dangers of excessive social media use, which may lead to anxiety and stress.